Condensation and coherence in condensed matter : proceedings of the Nobel Jubilee Symposium, Göteborg, Sweden, December 4-7, 2001 - Claeson, Tord; Delsing, P. (Per) (Physica scripta (Stockholm, Sweden : 1982) ;, 2003)
In 2001, the Nobel Foundation celebrated the 100th anniversary of the first Nobel Prize, and all previous Nobel laureates were invited to attend the Nobel ceremonies in Stockholm. This gave an excellent opportunity for arranging jubilee symposia with topics that would attract several of the laureates. The chosen subject of "Condensation and Coherence in Condensed Systems" attracted sixteen Nobel laureates and another thirty-five leading scientists.The idea was to bring scientists together from several related subdisciplines: atomic physics, quantum optics, and condensed matter physics, for cross-breeding of ideas, concepts, and experience. Subjects like phase transitions in strongly coupled systems, Bose-Einstein condensation in weakly coupled systems, macroscopic quantum phenomena, coherence in mesoscopic structures, and quantum information were intensively discussed from different points of view. Coherence phenomena in condensed systems were emphasized. A special session was devoted to the emerging field of quantum computing, with experimental and theoretical results reported for different types of qu-bits. The 2001 Nobel Prize awarded to Eric Cornell, Wolfgang Ketterle, and Carl Wieman, "for the achievement of Bose-Einstein condensation in dilute gases of alkali atoms, and for early fundamental studies of the properties of the condensates," gave an extra flavor to the theme of the Centennial Symposium.